Phygital approaches in the co-production of climate-resilient public open space: scoping review - Dina M. Saadallah; Sara M. Ibrahim; Hany M. Ayad (Proceedings of the Institution of Civil Engineers - Urban Design and Planning, 2026)
Public open spaces1 (POS) are fundamental to urban resilience, providing multifunctional, adaptable environments capable of addressing intensifying climatic challenges. As climate change accelerates, designing climate-resilient public open spaces2 (CRPOS) through active community involvement has become a planning imperative. Recent innovations have introduced ‘phygital’ methodologies integrating physical spatial interventions with digital technologies, including participatory geographic information system, digital twins, sensor networks, augmented reality, and online engagement platforms, enabling real-time feedback, simulation, and broader stakeholder inclusion. Despite substantial independent literature on POS design, climate adaptation, and smart-city technologies, research systematically examining how phygital approaches support CRPOS co-production through integrative participatory governance frameworks remains limited. This study conducts a structured scoping review critically synthesising literature at the intersection of POS co-production, climate resilience, and digitally mediated participation. Using a PRISMA-guided screening protocol alongside thematic, content, and narrative analyses, the review systematically maps prevailing themes, digital tools, and knowledge gaps. From 346 studies published between 2010 and 2024 across Scopus and Web of Science, 74 met the inclusion criteria. Findings illuminate how co-production, co-design, and co-creation collectively shape adaptive, inclusive public environments under climate stress, culminating in an integrative framework linking digital innovation, on-site engagement, and climate adaptation strategies.